Bicondylar Tibial Plateau Fractures: Assessing and Treating the Medial Fragment - Cherney, Steven; Gardner, Michael J. (The Journal of Knee Surgery, 2014)
Successful treatment of bicondylar tibial plateau requires focused and specific assessment and treatment of the medial fragment. Many fragment variations exist that help guide treatment. This may include posteromedial or medial plating using a variety of reduction and fixation techniques, or indirect reduction and lateral locked plating. With appropriate assessment, good results can be achieved.
Keywords: tibial plateau fractures; bicondylar; medial fragment